Prenatal arsenic exposure interferes in postnatal immunocompetence despite an absence of ongoing arsenic exposure. Issue 1 (1st January 2020) - Chakraborty, Mainak; Bhaumik, Moumita
Abstract: Arsenic (As) readily crosses the placenta and exposure of the fetus may cause adverse consequences later in life, including immunomodulation. In the current study, the question was asked how the immune repertoire might respond in postnatal life when there is no further As exposure. Here, pregnant mice (Balb/c [H-2 d ]) were exposed to arsenic trioxide (As2 O3 ) through their drinking water from time of conception until parturition. Their offspring, 4-week-old mice who had not been exposed again to As, were used for functional analyses of innate, humoral and cellular immunity. Compared to cells from non-As-exposed dam offspring, isolated peritoneal macro-phages (Mϕ) displayed no differences in T-cell stimulating ability. Levels of circulating IgG2a but not IgG1 were decreased in As-exposed dam offspring as compared to control offspring counterparts. Mixed-leukocyte reactions (MLR) indicated that CD4 + T-cells from the prenatal As-exposed mice were significantly less responsive to allogenic stimulation as evidenced by decreases in interferon (IFN)-γ and IL-2 production and in expression of CD44 and CD69 (but not CD25) activation markers. Interestingly, the Mϕ from the prenatal As-exposed mice were capable of stimulating normal allogenic T-cells, indicating that T-cells from these mice were refractory to allogenic signals. There was also a significant decrease in absolute numbers of splenic CD4 + and CD8 + T-cells due to prenatal As exposure (as compared to control). Lastly, the impaired immune function of the prenatal As-exposed mice was correlated with a very strong susceptibility to Escherichia coli infection. Taken together, the data from this study clearly show that in utero As exposure may continue to perpetuate a dampening effect on the immune repertoire of offspring, even into the early stages of postnatal life.